2018
DOI: 10.1002/cmdc.201800377
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Tripartin, a Putative KDM4 Natural Product Inhibitor, and 1‐Dichloromethylinden‐1‐ol Analogues

Abstract: The natural product tripartin has been reported to inhibit the N-methyl-lysine histone demethylase KDM4A. A synthesis of tripartin starting from 3,5-dimethoxyphenylacrylic acid was developed, and the enantiomers were separated by chiral HPLC. We observed that both tripartin enantiomers manifested an apparent increase in H3K9me3 levels when dosed in cells, as measured by western blot analysis. Thus, there is no enantiomeric discrimination toward this natural product in terms of its effects on cellular histone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Compound QC6352 (7) was reported to inhibit KDM4 with high efficacy in breast and colon cancer PDX models (Chen et al, 2017). Tripartin (8), the first natural histone lysine demethylase inhibitor (Kim et al, 2013;Guillade et al, 2018), has been recently re-evaluated and shown to cause substantial increase in H3K9me3 levels in HCT-116 cells by Western blot analysis, but either no inhibition or very mild inhibition when tested at 100 µM against isolated KDM4A, B, C, D, or E under standard assay conditions (Guillade et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Compound QC6352 (7) was reported to inhibit KDM4 with high efficacy in breast and colon cancer PDX models (Chen et al, 2017). Tripartin (8), the first natural histone lysine demethylase inhibitor (Kim et al, 2013;Guillade et al, 2018), has been recently re-evaluated and shown to cause substantial increase in H3K9me3 levels in HCT-116 cells by Western blot analysis, but either no inhibition or very mild inhibition when tested at 100 µM against isolated KDM4A, B, C, D, or E under standard assay conditions (Guillade et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…14 As JumonjiC KDMs use molecular oxygen as oxidizing agent for the demethylation reaction, a role in cellular oxygen sensing has also been discussed, e. g. for the subtype KDM6A. 15 JmjC histone demethylases have emerged as promising drug targets, 1,[16][17][18][19][20] with inhibitor discovery programs being reported by us [21][22][23][24][25][26][27] and others, [28][29][30][31][32][33][34][35] as recently reviewed. 17,19,[36][37][38][39][40] The majority of reported JmjC KDM inhibitors function by active site metal chelation and competitive displacement of the co-substrate 2OG.…”
mentioning
confidence: 99%
“…Importantly, plenty of natural compounds are known to interfere with epigenetic processes; for example, flavonoids are compounds found in black raspberry (and many other plants) which inhibit DNA methyltransferase 1 (DNMT1) activity and enhance the expression of tumor suppressor genes ( Wang et al, 2013 ). Nevertheless, although there are reports about natural molecules that could interfere with KDM4 subfamily activity, no direct natural inhibitors are known so far ( Guillade et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tripartin, a compound produced by a bacteria found in dung beetles, is the only natural inhibitor reported for the KDM4 subfamily ( Kim et al, 2013 ). However, another study showed that tripartin and its analogs increased H3K9me3 levels but did not directly interact with KDM4 proteins, suggesting that their mechanisms of action could involve other enzymes ( Guillade et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%